Gambaran Hasil Analisis Sefalometri Pada Pasien Ras Deutro Melayu Usia 8-12 Tahun Menggunakan Analisis Ricketts - Rissa Anuar Shindy; Olivia Piona Sahelangi (Fakultas Kedokteran Gigi Universitas Trisakti, 2020)
Background: Cephalometric analysis is one of the supporting tools in establishing a correct diagnosis. From the various methods of cephalometric analysis, one that used is the analysis of Ricketts. This Ricketts analysis has a method for determining the position of facial convexity, dental position and face profile. This study was thus carried out to describe the value of cephalometric measurements in patients with Deutro Melayu race aged 8-12 years using Ricketts analysis. Method: This type of research is a descriptive observational cross sectional design. Samples were taken in the form of secondary data, namely cephalograms from orthodontic patients at RSGM FKG Usakti in January 2018 to December 2018. The analysis was carried out by measuring 8 Ricketts analysis parameters, namely: facial axis, facial depth, mandibular plane, convexity of point A, lower incisor to A-Pog, upper molar to PtV, lower incisor to A-Pog, lower lip to aesthetic lines. Result: Based on Ricketts analysis, the cephalometric mean value of RSGM FKG Usakti orthodontic patients was facial axis of 87,8°; facial depth of 85,6°; mandibular plane of 31°; convexity of point A 3,5 mm; the lower incisor distance to A-Pog of 3,0 mm; upper molar to PtV of 7,8 mm; the lower incisor angle to A-Pog of 23,5°; lower lip to aesthetic lines of 1,9 mm. Conclusions: Deutro Malay Race has a skeletal class 1 with a tendency towards lower incisor proclination and mild protusive lower lips.